2020
DOI: 10.3389/fpls.2020.00731
|View full text |Cite
|
Sign up to set email alerts
|

Searching for FHB Resistances in Bread Wheat: Susceptibility at the Crossroad

Abstract: Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is one of the most devastating fungal wheat diseases. During the past decades, many efforts have been deployed to dissect FHB resistance, investigating both the wheat responses to infection and, more recently, the fungal determinants of pathogenicity. Although no total resistance has been identified so far, they demonstrated that some plant functions and the expression of specific genes are needed to promote FHB. Associated with the increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 107 publications
(109 reference statements)
1
25
0
Order By: Relevance
“…By contrast, we observed that the TaMRP-D1 variants were linked to the FHB and mycotoxin resistance in the cultivars with the non-semi-dwarf allele of Rht8 . The efficient use of this FHB-QTL on the 2DS region as breeding resource requires the breaking of the linkage drag between the FHB-QTL and semi-dwarfism ( Basnet et al 2012 , Niwa et al 2018 , Fabre et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, we observed that the TaMRP-D1 variants were linked to the FHB and mycotoxin resistance in the cultivars with the non-semi-dwarf allele of Rht8 . The efficient use of this FHB-QTL on the 2DS region as breeding resource requires the breaking of the linkage drag between the FHB-QTL and semi-dwarfism ( Basnet et al 2012 , Niwa et al 2018 , Fabre et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular nature of many QTLs on the FHB-resistant gene is yet to be studied ( Handa et al 2008 , Niwa et al 2018 ). The use of FHB-QTL in 2DS, another gene resource for the FHB resistance of Asian germplasms ( Basnet et al 2012 , Niwa et al 2018 , Fabre et al 2020 ), was hampered by its linkage to the non-semi-dwarf allele of Rht8 and so will be facilitated by further studies to allow pyramiding the FHB-resistant alleles. We propose that the de novo genome assembly of Norin 61 will open the way to analysis of the functional variants and evolution of East Asian wheat.…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have shown that different mutations inducing the TaHRC gene loss of function explain part of this Fhb1-mediated resistance (Li et al, 2019;Su et al, 2019), further works have either suggested a role for the WFhb1-1 gene through its potential antifungal activity (Paudel et al, 2020) or for the TaLAC4 gene whose mutation leads to an increase of FHB susceptibility (Soni et al, 2020). In addition to the current sources of FHB resistance, several works introduced alternative forms of resistance via the identification of wheat genes involved in the success of the disease (reviewed in Fabre et al, 2020). By definition, any plant gene that facilitates infection and that promotes compatibility with pathogens can be considered as a susceptibility gene (van Schie and Takken, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tests in different environmental conditions are needed to verify the susceptibility of wheat germplasm to FHB as the severity of the disease is influenced by climatic conditions and may result in a large variability of the interaction between genotype and environment [ 5 , 14 ]. Over 500 quantitative trait loci (QTLs) conferring small to moderate effects on the different FHB resistance types have been reported in wheat [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%